Handbook of Child Psychology and Developmental Science 2015
DOI: 10.1002/9781118963418.childpsy320
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Development

Abstract: How does human behavior come to be gendered, and how do gendered behaviors change or remain stable over time? Although men and women, as well as girls and boys, are largely similar psychologically and behaviorally, there are some areas of gender difference. These include gender identity; sexual orientation; childhood play behaviors, such as toy, playmate, and activity preferences; personality characteristics, such as aggression and empathy; and some specific spatial, mathematical, and verbal abilities. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 437 publications
0
57
0
Order By: Relevance
“…In humans, aggression is defined as behavior, typically directed toward another individual, that is carried out with the intent of causing harm (Bushman & Anderson, 2001) and activity level is defined as the typical level of energy that an individual expends through movement (Eaton & Enns, 1986). There is general agreement that gender differences in human behavior result from a combination of genetic, early hormonal and socio-cultural influences (Hines, 2015; Leaper, 2013). The current investigation examines the relation of the gonadal steroid, testosterone, prenatally to later aggression and activity level in children.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, aggression is defined as behavior, typically directed toward another individual, that is carried out with the intent of causing harm (Bushman & Anderson, 2001) and activity level is defined as the typical level of energy that an individual expends through movement (Eaton & Enns, 1986). There is general agreement that gender differences in human behavior result from a combination of genetic, early hormonal and socio-cultural influences (Hines, 2015; Leaper, 2013). The current investigation examines the relation of the gonadal steroid, testosterone, prenatally to later aggression and activity level in children.…”
Section: Introductionmentioning
confidence: 99%
“…Although the behaviour of human males and females is largely similar [1], there are some characteristics that differ on average for men and women or boys and girls [2]. One area of robust gender difference involves children's play behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Theories of human gender development describe developmental systems involving multiple causative factors working together over time [2,24]. However, despite the evidence that hormonal, social and cognitive mechanisms all influence human gender development, there is almost no information on how they work together.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the observational literature on gender and social competence is comparably smaller, several studies have underscored the importance of gender in defining social norms across child development (i.e., social norms vary by age and gender; see Hines, 2015). For example, sex-segregation of the peer group, namely whether a child interacts with same-sex peers over opposite-sex peers, has been shown to increase as children grow older; one study found that preschool-age children interact 3 times more with same-sex peers than opposite-sex peers, and by elementary school, that difference has increased to a factor of 10 (Maccoby & Jacklin, 1987).…”
Section: Development Of Social Interactions: Influence Of Age and Gendermentioning
confidence: 99%